Implementation Of E-Commerce With Business Model Canvas (BMC) Method To Increase Sales In Detak Original Store: Implementasi E-Commerce Dengan Metode Business Model Canvas (BMC) Untuk Meningkatkan Penjualan Di Detak Original Store - Dzikri Febrian; Atik Ariesta; Dyah Retno Utari (Universitas Singaperbangsa Karawang, 2022)
Detak Original store is engaged in selling men's clothing products that have physical stores in Tanah Abang and online sales in marketplaces such as Tokopedia, Lazada, Shopee, and social media Instagram. Problems that occur are a lot of competition in the current marketplace during the Covid-19 pandemic, decreased revenue in physical stores as a result of the difficulty of direct sales during the pandemic, less than optimal sales promotion so that old goods are difficult to sell, lack of detailed product information so that customers become hesitant to buy products via the marketplace and Instagram. Other problems are less than optimal in finding sales report data because the products are similar to one another. Therefore, Detak Original wants to create its own website with an E-commerce system to maximize sales. The method used in building a new E-Commerce business is the Business Model Canvas (BMC) method, and system design using UML and a website with Wordpess-based Content Management System (CMS). This research resulted in an E-Commerce website with various available features to facilitate the long distance buying and selling process. By easily accessing the E-Commerce website, the buying and selling process will be effective and efficient to connect with the public and increase sales.